2023
DOI: 10.1021/acsami.3c02278
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric-on-Dielectric Achieved on SiO2in Preference to W by Water-free Chemical Vapor Depositions with Aniline Passivation

Abstract: Selective and smooth dielectric-on-dielectric was achieved by water-free single-precursor chemical vapor deposition (CVD) processes with the help of aniline passivation. Aniline selective passivation was demonstrated on W surfaces in preference to SiO 2 at 250, 300, and 330 °C. After aniline passivation, selective HfO 2 , Al 2 O 3 , and TiO 2 were deposited only on the HF-cleaned SiO 2 surface by water-free single-precursor CVD using hafnium tert-butoxide Hf(O t Bu) 4 , aluminum-tri-sec-butoxide (ATSB), and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 33 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…In previous studies on water-free selective oxide deposition, water-free pulsed CVD has been shown to exhibit faster growth on metal surfaces compared to SiO 2 . 8 This phenomenon is particularly evident on W metal surfaces, which tend to undergo oxidation. Because of this facile oxidation, W has a propensity to favor the formation of hydroxyl groups and oxide layers.…”
Section: Aniline Passivation and Tbs Reactivity On Different Surfacesmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies on water-free selective oxide deposition, water-free pulsed CVD has been shown to exhibit faster growth on metal surfaces compared to SiO 2 . 8 This phenomenon is particularly evident on W metal surfaces, which tend to undergo oxidation. Because of this facile oxidation, W has a propensity to favor the formation of hydroxyl groups and oxide layers.…”
Section: Aniline Passivation and Tbs Reactivity On Different Surfacesmentioning
confidence: 99%
“…Because of this facile oxidation, W has a propensity to favor the formation of hydroxyl groups and oxide layers. 8 To inhibit oxide growth on metals and allow growth on dielectrics, aniline passivation is required. The passivation ability of aniline was tested on HFcleaned SiO 2 , degreased Si 3 N 4 , and degreased W substrates with the pulsed AlO x (ATSB) CVD.…”
Section: Aniline Passivation and Tbs Reactivity On Different Surfacesmentioning
confidence: 99%
See 3 more Smart Citations